Knowledge, attitudes and practices of young adults towards HIV prevention: an analysis of baseline data from a community-based HIV prevention intervention study in two high HIV burden districts, South Africa - Simukai Shamu; Sikhulile Khupakonke; Thato Farirai; Jean Slabbert; Thato Chidarikire; Geoffrey Guloba; Nkhensani Nkhwashu (BMC, 2020)
Abstract Background With an HIV incidence of 1.00 skewed against women (1.51), adolescents in South Africa are at high HIV risk. This paper assesses young adults' (18-24 years) knowledge, attitudes and practices regarding HIV prevention in Nkangala and OR Tambo districts. Methods A cross-sectional household survey was conducted in two districts in 2017/8. Participants completed computer-assisted self-interviews on HIV knowledge, attitudes, behaviour practices, use of social media and condom use at last sex (proxy for high-risk sex). HIV knowledge was assessed using the South African-adapted UNAIDS scale. Descriptive analyses were conducted and logistic regression models were built to assess factors associated with being knowledgeable of HIV and condom use at last sex. Results One thousand nine hundred fifty-five participants were interviewed (90% response rate). Less than half (44.7%) had correct knowledge of HIV prevention and 73% used a condom at last sex. Social media use predicted high HIV knowledge as higher odds were observed among participants using the print media (aOR1.87; 1.34-2.60), WhatsApp (aOR1.55; 1.26-1.90), radio/television (aOR2.75; 1.15-6.55) although social networking sites' use protected against knowledge acquisition (aOR0.53; 0.34-0.82). Females (aOR0.75; 0.58-0.97) and participants reporting sexual risk were less likely to have HIV knowledge as negative associations were found for having multiple sexual partners in the last 3 months (aOR0.63;0.48-0.82) and ever having sex (aOR0.37;0.23-0.61). Participants who abused drugs (aOR1.40; 1.05-1.88) and had attitudes accepting people living with HIV (aOR2.05; 1.14-3.69) had higher odds of having HIV knowledge. Females (aOR0.70; 0.54-0.91), students (aOR0.52; 0.40-0.66) and participants who abused drugs (aOR0.58; 0.43-0.77) were less likely to report condom use at last sex. Conclusions There is a correlation between media use and HIV knowledge, non-condom use and HIV knowledge, and high-risk sexual behaviours and less HIV knowledge. An aggressive community media campaign utilising locally available, preferred and accessible media platforms among young adults is required for behaviour change.